A Review of Research and Development Evaluation Across the Globe (Journal of Business Management and Accounting, 2015)
In  view  of  the  present  rapid  changing  of  technology  and  economic  landscapes,  the Research and Development (R&D) field has garnered more attention than before throughout the world. Industrial innovation in this knowledge-driven era demands R&D as the undisputable key for improvement  and  to  maintain  competitiveness.  Parallel  to  the  industrial  and  economic growths,  more  and  more  researchers  and  skilled  workers are  required  to  fill  in  the  specific fields  all  over  the  globe.  The  growing  numbers  of  R&D facilitiesand  personnel,  however,  is unable  to  provide  assurance  that  improvement would  take  place  after  a  particular  research result  is  implemented.  R&D  laboratories themselves  are  systems  that  process  inputs  and generate  outputs,  where  in  the  process,  inevitable challenges  are  encountered  to  ensure  that the  task  is  not  only  capable  of solving  particular  problems,  but  also  to  ensure  positive  and innovative   outcomes.   R&D is   also   subject   to   performance   analysis   to   measure   the effectiveness,  accomplishments,  and  productivity  amongst  others,  because  performance  is  an importance  element  in grant  disbursement.  In  doing  so,  R&D  evaluation  is  an  important aspect  and  practised in  most  parts  of  the  world  with  different  methods  and  strategies.  This paper  reports an  R&D  overview  and  explores  the  need  of  the  global  community  for  post decision evaluation to ensure that the decision is sustainable in the long run.